Market Structure analysis with Herfindahl-Hirchman Index and Lauraéus-Kaivo-oja Indices in the Global Cobotics Markets - Lauraëus Theresa; Kaivo-oja Jari; Knudsen Mikkel Stein; Kuokkanen Kimmo (Sciendo, 2022)
Research purpose. The study is focused on the expected market dynamics of global cobotics markets. This study investigates the current market structure of the global cobotics market. The scientific aim of the research is to report the first data-based market structure analysis of the global cobotics market with the HHI index and with the LKI index analysis. With analysis we are able to show the diversification rate of the global cobotics market.
Design / Methodology / Approach. The methodology is based on conventional statistical index theory and statistics. The methodology is the calculation of the Herfindahl-Hirchman Index and the Lauraéus-Kaivo-oja Index. The authors compare the results of these two methodologies.
Findings. The Herfindahl-Hirschman Index (HHI) and the Lauraéus-Kaivo-oja Index are statistical measures of market concentration, and they can be used to determine market competitiveness. This paper demonstrates novel data analytics possibilities of new market data collected by the Statzon, Ltd with various comparative analytical results and findings. By our analyses we can help multiple industrial stakeholders make faster decisions and better strategic plans with the easiest and fastest access to accurate, reliable, and up-to-date cobotics industry statistics, forecasts, and insights. The finding is that this study reveals the current market structure of global cobotics. It is a novel finding and result.
Originality / Value / Practical implications. This paper demonstrates the novel and exciting possibilities of transparent index calculation tools. The authors provide original results. Authors underline that extra value added to stakeholders and customers will be provided by joint data pooling strategy of various data sources, which is a key approach of this paper. Real-time market structure analyses create reliable and knowledge-based information for decision-makers and stakeholders of the global cobotics industry.
Keywords
Market trends
Market structure of global cobotics market
Herfindahl-Hirschman Index (HHI)
Lauraéus-Kaivo-oja Index (LKI)
Market data analytics
JEL Classification
C13
C53
C63
D52
G28